1998
DOI: 10.1002/(sici)1097-4679(199806)54:4<439::aid-jclp6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in factor structure of the Self-Administered Alcoholism Screening Test

Abstract: Recent studies have revealed differences between men and women alcoholics in symptoms, consequences, and help-seeking behavior related to alcohol usage. Based on these findings, it was hypothesized that gender differences also would appear on alcohol screening instruments. The Self-Administered Alcoholism Screening Test (Colligan, Davis, & Morse, 1988: SAAST: Swenson & Morse, 1975) of 1,920 men and 1,775 women was subjected to a within-gender, principle-components, factor analysis with a varimax rotation. Gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Studies have shown the ratio of male to female users of alcohol is 1.3 ( Sadock, Sadock, & Ruiz, 2000 ). This result conforms to those we have found and to those from other researches carried out in Iran ( Allen et al, 1998 ). The lower frequency of alcohol use in women may rely on various reasons, possibly cultural, social, and religious.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown the ratio of male to female users of alcohol is 1.3 ( Sadock, Sadock, & Ruiz, 2000 ). This result conforms to those we have found and to those from other researches carried out in Iran ( Allen et al, 1998 ). The lower frequency of alcohol use in women may rely on various reasons, possibly cultural, social, and religious.…”
Section: Discussionsupporting
confidence: 93%
“…PCA and factor analysis are the most widely used statistical methods to reduce the number of dimensions in data analysis and to investigate multiple intercorrelations between variables. [13][14][15]18 It has also been used to define similar and deviating responses among biological data (variables). [19][20][21][22][23] Results of the multiple intercorrelation analysis of the data in Table 1 are displayed in Table 2A (correlation matrix) and Table 2B (factor loadings of the 7 variables).…”
Section: Statistical Comparison Of the Results Of The Mtt Atp And Calcein Assaysmentioning
confidence: 99%
“…The data matrix that contains pIC 50 values (= -logIC 50 ) was analyzed by principal component analysis. [13][14][15] In contrast to previously published articles, which compared 2 parameters only, 12,16 the principal component analysis applied here allows to directly compare more than 2 variables, namely, data of the MTT, ATP, and calcein assays in the 3 different cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…There was no SAAST‐R item for which females had a higher endorsement rate than males in either criterion group. In contrast, using the original SAAST, researchers had found female inpatients were more likely to endorse occupationally and socially disruptive behaviors, while male inpatients were more likely to endorse loss of control and report concern from others about their drinking 39,42 . They also found women were more likely than men to report emotional problems as a consequence of their drinking.…”
Section: Discussionmentioning
confidence: 95%